Simulation and Analysis of Single-Electron Transistors (SETs) Using TCAD and Virtuoso Framework: Advancing Low-Power Nanoelectronics - Anil Kumar (Innovative Research Thoughts, 2017)
Single-electron transistors (SETs) are pivotal in advancing nanoelectronics due to their extremely low power consumption and unique electron transport characteristics. This research paper presents a comprehensive simulation and analysis of SETs using Technology Computer Aided Design (TCAD) and Virtuoso framework. We explore the device layout, including intrinsic type channel structures and material specifications, and simulate the electrical behavior of SETs under various conditions. Our findings highlight the influence of gate voltage, electron mobility, and temperature on device performance. Additionally, we discuss the Coulomb blockade effect and its impact on SET operation. The results demonstrate the potential of SETs for low-power digital circuit applications, emphasizing their significance in future nanoelectronic circuits.